Gammaropsis (Podoceropsis) grasslei (Amphipoda: Photidae) a new species of commensal amphipod of the deep-water lithodid Neolithodes diomedeae from the Guaymas Basin, Gulf of California - Soto, Luis A.; Corona, Adriana (Zootaxa, 2007)
A new species of commensal amphipod from the hydrothermal vent system of Guaymas Basin is described. Gammaropsis (Podoceropsis) grasslei was recovered from the carapace of the deep-water lithodid Neolithodes dioemedeae. It differs from other Gammaropsis (Podoceropsis) in exhibiting a longer palm of the second gnathopod of male, a highly ornamented entire and fleshy telson and the dense ornamentation of the maxillas.